(untitled) (Bangladesh Journal of Animal Science, 2016)
The aim of the study was designed to investigate the socio-economic status of buffalo farmers, productive and reproductive performances and management practices of buffaloes at different villages of Lalpur Upozila of Natore district in Bangladesh. For this investigation total one hundred twenty buffalo farmers were selected from twelve villages. Ten farmers who have at least five buffaloes were randomly selected from each village. The investigation revealed that majority of the buffalo farmers was below 30 years of age. Fifty five percent farmers were educated and remarkable number of farmer (40%) were reared only livestock. More than 80 % of the farmer holding 2 to 5 acres of land, and maximum farmers belonged to medium income categories. Sixty eight percent of the farmers took bank loan and/ or NGO loan for rearing buffaloes. Most of the farmers practiced buffalo rearing as their family profession. The buffalo of this area was mostly crossbred types. The highest numbers of buffaloes found were heifer. More than 80% of the farmer kept their female buffaloes above five years. In this study area the average milk production of buffalo was 3.32L/d. Birth weight of crossbred buffalo calves was 30.5 kg, weaning and slaughter age of buffaloes in selected areas were 16 and 57 months respectively. The average age at first heat was 3.47 years. The gestation period, number of service per conception, post partum hear period and inter calving period was 10 months, 3.42 times, 5.31 and 13.5 months, respectively. Most of the farmers maintain their buffaloes mainly in extensive system, and availability of the feeds and fodder was the major problem for buffalo rearing. Most of the farmers were fully depend on river bed (char) grasses and grazing their buffaloes 5-7 hours. Out of locally available feeds and fodders rice straw, river bed grasses and sugarcane top were the main source of feeds for buffaloes. The CP content of baghata grass was found higher compared to other unconventional grasses. Incidence of diseases, foot and mouth diseases was high and farmers did not follow any vaccination and de-warming programme. The annual cost of production per buffalo was Tk. 8741.50 while a gross return per buffalo was Tk. 25028.50. The annual educational capacity increased of the buffalo farmers was 63% but other parameters were also increased through buffalo rearing. Considering all this parameters related to livelihood, it was clearly found that the socio-economic status of the buffalo farmers was improved through buffalo rearing. Bang. J. Anim. Sci. 2015. 44 (3):157-165